CASE STUDY: HISTORY LEARNING BASED ON INDEPENDENT CURRICULUM AT STATE SENIOR HIGH SCHOOL 1 BOTUMOITO - Nihe, Riyanto; Mondong, Tonny Iskandar; Hotimah, Iis Husnul (CV. Fahr Publishing, 2025)
This study aims to understand the implementation of the Independent Curriculum in history learning at SMA Negeri 1 Botumoito and identify the factors that influence it. This study uses a qualitative research method with a descriptive approach, data collection is carried out through observations of classroom learning and the Pancasila Student Profile (P5) project, interviews with parties related to the implementation of the Independent Curriculum in the context of history learning, and analysis of documentation of activities and supporting archives. The results of the study indicate that the implementation of the Independent Curriculum at SMA Negeri 1 Botumoito has not reached its optimal stage. This condition is influenced by the unequal understanding among subject teachers regarding the essence of the Independent Curriculum. Furthermore, the practice of differentiated learning, which is the core of the Independent Curriculum, has not been applied consistently due to time constraints, established teaching habits, and limited references and adequate training, so that learning is not fully centered on students.